THE ASSOCIATION OF FUNCTION, MOOD, AND LONELINESS WITH SURVIVAL IN OLDER ADULTS WITH HEMATOLOGIC MALIGNANCIES. (11th November 2018) - DuMontier, C; Murillo, A; Liu, M; Hshieh, T; Soiffer, R; Stone, R; Abel, G; Driver, J
Abstract: Patient-reported outcomes are important measures of quality of life as well as predictors of survival in older cancer patients, yet they are rarely measured in clinical practice. Our study prospectively assesses the association of patient-reported function, depression, and loneliness with survival in older adults with hematologic malignancies. We approached all patients >/=75 years-old presenting for consultation in the leukemia, lymphoma, or myeloma clinics at a tertiary referral center between 2/1/2015 and 11/20/2017. 480/558 (86.0%) patients consented and were included in the study. We measured patient-reported dependence in activities of daily living (ADLs), dependence in instrumental activities of daily living (iADLs), depression, and loneliness. The average age was 79.7 +/- 4.0 SD. 179 (37.2%) had aggressive malignancies, 239 (53.5%) were receiving intensive treatment at the time of assessment, and the average Charlson comorbidity score was 3.5 +/- 1.8 SD. Independent of these baseline characteristics, patients with at least one dependency in either ADLs or iADLs had a higher risk of death [hazard ratio (HR)=2.38, 95% confidence interval (CI)=1.57–3.60] compared to those without dependencies. Self-reported depression was also independently associated with higher mortality (HR=1.56, 95% CI=1.02–2.38), however, loneliness was not (HR=1.21, 95% CI=0.73–2.02). Patients with both aggressive cancer and functional dependency had worse survival than those with non-aggressive cancer and functional dependency (HR=3.45, 95% CI=1.84–6.49 vs. HR=1.35, 95% CI=0.71–2.56; joint test for interaction p-value<0.05). Assessing patient-reported functional status and depression in older adults with hematologic malignancies may be important for not only their quality of life but also their survival.